Use of information technologies in management of technological processes in pig farming - Semenov, O.; Lysychenko, M.; Khandola, Yu. (Energy and Automation, 2025)
The main problem of the industry over the past two decades is the reduction of the pig population and pig production in Ukraine. Industrial pig farming suffered the greatest losses; according to statistical data, the number of livestock decreased by 3.6 times, while the share of private farms is 49% of the total livestock. Due to non-technological methods of raising animals, the indicators of average daily gains and the yield of viable offspring per sow in Ukraine are significantly lower than the world averages. Therefore, the further development of pig farming is associated with the technical and technological reconstruction of the industry through the construction of new and deep reconstruction of pig farms, modernization or replacement of animal husbandry technology. To do this, it is necessary to apply innovative resource-saving technologies aimed at intensifying the growing process based on the use of its own feed base and switching to a production cycle of 182-189 days with weaning of piglets at 21-35 days, rearing for 40-56 days and fattening for 105-112 days. The purpose of the study is to develop an automated system for real-time monitoring of technological processes for maintaining microclimate parameters, dosing of feed or feed mixtures and the process of irradiation of pigs with ultraviolet radiation in the premises of the piggery when keeping animals of different ages through the use of a complex mobile installation for obtaining information about the biophysical characteristics of animals in each box of the premises. The authors proposed a technical solution, which is built on the basis of the use of the "pattern recognition theory", determining the geometric dimensions of animals using the stereopsis method. The design of the complex installation allows for movement once a day, recommended during the break after lunchtime feeding, when the animals are resting. Key words: information technology, young pigs, ultraviolet radiation, irradiation installations, automatic control, pattern recognition